Is degradation of dyes even possible without using photocatalysts? – a detailed comparative study. Issue 53 (30th November 2022) - Sen, Subhadeep; Das, Chanchal; Ghosh, Narendra Nath; Baildya, Nabajyoti; Bhattacharya, Sumantra; Khan, Moonis Ali; Sillanpää, Mika; Biswas, Goutam
Abstract : Degradation of cationic dyes through self generation of ROS. Abstract : Herein, catalyst-free, eco-friendly, photo-triggered, self-degradation of malachite green (MG) and crystal violet (CV) dyes in comparison to photocatalytic degradation were investigated. To the best of our knowledge, this is the first systematic study to demonstrate the reactive oxygen species (ROS), electron (e − ) and hole (h + ) generation ability of dyes to initiate self-degradation in the presence of direct solar energy (a free source of UV radiation) and UV light (254 and 365 nm). Various experimental conditions, e.g., different dye concentrations, pH, vessel-materials (borosilicate glass and quartz) were optimized to achieve the optimum degradation outcomes. The degradation kinetics of dyes suggested the applicability of second-order-kinetics to all kinds of applied light sources. Investigation of the thermodynamic approach reveals that the self-degradation procedure was endothermic, with activation energies of 46.89 and 52.96 kJ mol −1, respectively, for MG and CV. The self-degradation mechanism was further corroborated by the quantum calculations, while the formation of final degraded products for dye-degradations was established on the basis of mass spectroscopy and total organic carbon (TOC) analysis. The computed emission energies for MG and CV advocate that the excitation energy occurs due to the sole-attribution electron excitation from the Highest Occupied Molecular Orbital (HOMO) to the Lowest Unoccupied Molecular Orbital (LUMO). The close energy difference between the hydroxyl anions and the dyes also facilitates the creation of the hydroxyl radical. In a similar manner, the excited electrons from the aforementioned dyes may readily be transferred to triplet molecular oxygen, which makes it possible to generate super oxide. The radical generated in the process facilitates the self-degradation of the dyes.